2008
DOI: 10.1074/jbc.m803319200
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal Tail of FGF19 Determines Its Specificity toward Klotho Co-receptors

Abstract: FGF19 subfamily proteins (FGF19, FGF21, and FGF23) are unique members of fibroblast growth factors (FGFs) that regulate energy, bile acid, glucose, lipid, phosphate, and vitamin D homeostasis in an endocrine fashion. Their activities require the presence of ␣ or ␤Klotho, two related single-pass transmembrane proteins, as co-receptors in relevant target tissues. We previously showed that FGF19 can bind to both ␣ and ␤Klotho, whereas FGF21 and FGF23 can bind only to either ␤Klotho or ␣Klotho, respectively in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 20 publications
7
59
0
Order By: Relevance
“…Moreover, klotho gene can transcribe a secreted form of klotho by alternative RNA splicing encoding only the KL1 domain (13,14,23). Only full-length klotho can function as a coreceptor for FGF23 (19,44). Indeed, KL1 did not affect signaling by FGF23 in MDCT cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, klotho gene can transcribe a secreted form of klotho by alternative RNA splicing encoding only the KL1 domain (13,14,23). Only full-length klotho can function as a coreceptor for FGF23 (19,44). Indeed, KL1 did not affect signaling by FGF23 in MDCT cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since both FGF19 and FGF21 bind to ␤Klotho, it raised the question whether these ligands bind to a shared site on ␤Klotho or whether each ligand has its own distinct binding site. Previous studies have suggested that, reminiscent of FGF23, FGF19 and FGF21 use their C-terminal tail to bind ␤Klotho (41,73,75). Based on this knowledge, we set up an SPR-based competition binding assay to examine whether the isolated C-terminal tail peptide of FGF19 (FGF19 C-tail [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This requirement for either ␣Klotho or ␤Klotho provides another level of selectivity to FGFR signaling and may restrict the target tissues for this endocrine FGF subfamily. We showed that the Klotho-interaction domain of FGF19 subfamily members resides in their C-terminal region (12). The sole exception for this co-receptor requirement is the ability of FGF19 to bind directly to FGFR4, but not to other FGFRs, in the absence of the Klothos (11,13).…”
mentioning
confidence: 97%